(untitled) (Eurasian Scientific Herald, 2022)
Powers of compensating devices for electrified railway power supply systems can be provided with certain technical conditions. In this case, optimal distribution of reactive power within the system is required. This problem can be solved, for example, by the Lagrangian method. In the power supply scheme, compensating devices with a certain value of power should be distributed among the nodes of the electric network in such a way that it is necessary to achieve a minimum wastage of active power